Effect of Soil and Structure Nonlinear Interaction on the Efficiency of Tuned Mass Damper - Hamid Masaeli; Mehdi Panahi (Salehan Institute of Higher Education, 2018)
In this paper, three 10, 15, and 20-story two-dimensional concrete structures have been used with a moment frame bearing system as models under analysis. First, using various time history analyses by the OpenSees software, the optimal parameters of the tuned mass damper (TMD), including frequency and mass, were obtained. Structures controlled with and without TMD were modelled on three soft, moderate, and hard soil types classified according to Code 2800. The models were analyzed in terms of time history by 7 ground motions. In order to take into account the nonlinear interaction of soil and structure, the model of the beam on nonlinear Winkler foundation has been used. The results show that nonlinear interaction in most cases reduces the efficiency of TMD. Moreover, as the soil becomes softer, the efficiency reduction of the mass damper increases.